When Emotion Blinds: A Spatiotemporal Competition Account of Emotion-Induced Blindness - Wang, Lingling; Kennedy, Briana L.; Most, Steven B. (Frontiers in Psychology, 2012)
Emotional visual scenes are such powerful attractors of attention that they can disrupt perception of other stimuli that appear soon afterwards, an effect known as emotion-induced blindness. What mechanisms underlie this impact of emotion on perception? Evidence suggests that emotion-induced blindness may be distinguishable from closely related phenomena such as the orienting of spatial attention to emotional stimuli or the central resource bottlenecks commonly associated with the attentional blink. Instead, we suggest that emotion-induced blindness reflects relatively early competition between targets and emotional distractors, where spontaneous prioritization of emotional stimuli leads to suppression of competing perceptual representations potentially linked to an overlapping point in time and space.